1975
DOI: 10.1128/jb.124.1.7-13.1975
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of toluene and xylenes by Pseudomonas (putida (arvilla) mt-2: evidence for a new function of the TOL plasmid

Abstract: Pseudomonas putida (arvilla) mt-2 carries genes for the catabolism of toluene, m-xylene, and p-xylene on a transmissible plasmid, TOL. These compounds are degraded by oxidation of one of the methyl substituents via the corresponding alcohols and aldehydes to benzoate and m-and p-toluates, respectively, which are then further metabolised by the meta pathway, also coded for by the TOL plasmid. The specificities of the benzyl alcohol dehydrogenase and the benzaldehyde dehydrogenase for their three respective subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
212
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(219 citation statements)
references
References 18 publications
7
212
0
Order By: Relevance
“…A more realistic approach is to engineer soil bacteria that are known to survive in contaminated environments for an extended period. Of particular interest is Pseudomonas putida KT2440, which is a derivative of the TOL-pathway-containing P. putida mt-2 (12). This bacterium is robust and ubiquitous in soils and is capable of using a variety of pollutants such as toluene and xylene.…”
Section: Introductionmentioning
confidence: 99%
“…A more realistic approach is to engineer soil bacteria that are known to survive in contaminated environments for an extended period. Of particular interest is Pseudomonas putida KT2440, which is a derivative of the TOL-pathway-containing P. putida mt-2 (12). This bacterium is robust and ubiquitous in soils and is capable of using a variety of pollutants such as toluene and xylene.…”
Section: Introductionmentioning
confidence: 99%
“…The P. putida mt-2 strain (ATCC 33015;Worsey and Williams, 1975) or the pWW0-lacking derivative P. putida KT2440 (Nelson et al, 2002) were used in this study. P. putida strains were grown at 30 C either in LB or in M9 minimal medium (Sambrook and Russell, 2001) supplemented with succinate (0.4%), glucose (0.3%) or fructose (0.3%) as a carbon source.…”
Section: Methodsmentioning
confidence: 99%
“…Degradation of m-xylene and other aromatic hydrocarbons by the soil bacterium Pseudomonas putida mt-2 is made possible by the action of the xyl genes borne by plasmid pWW0 (Worsey and Williams, 1975;Greated et al, 2002). As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that several metabolic intermediates of certain aromatic hydrocarbons, such as benzene 618 and toluene, are potential carbon sources for aromatic hydrocarbon degraders. 12,16*26, 36 These intermediates are, in general, products from the initial steps of biodegradation of the aromatic hydrocarbons. GrbiC-GaliC and Vogel l 6 reported that phenol was the major aromatic intermediate in mixed methanogenic cultures fed with benzene, while o-cresol, p-cresol and benzoic acid were intermediates in the same cultures fed with toluene.…”
Section: Other Aromatic Hydrocarbons As Carbon Sourcesmentioning
confidence: 99%